2018
DOI: 10.18632/oncotarget.25258
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in prognosis of distant recurrence in HR-positive and HER2-negative breast cancer patients

Abstract: There had been several studies using gene-expression profiling in predicting distant recurrence in breast cancer. In this study, we developed an 18-gene classifier (18-GC) to predict distant recurrence of breast cancer and compared it with the 21-gene panel (Oncotype DX®, ODx) in performance. Included were 224 breast cancer patients with positive hormonal receptor (HR+) and negative human epidermal growth factor receptor 2 (HER2-). We compared the demographic, clinical, and survival information of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…One such report suggested CTCs to possibly be an indicator of the therapeutic effect of chemotherapy or endocrine therapy [32], whereas some other studies reported them as a predictor of distant metastatic recurrence of breast cancer based on clinical deta [33,34]. Some publications have even reported the prediction of distant metastasis using genetic assays [35].…”
Section: Discussionmentioning
confidence: 99%
“…One such report suggested CTCs to possibly be an indicator of the therapeutic effect of chemotherapy or endocrine therapy [32], whereas some other studies reported them as a predictor of distant metastatic recurrence of breast cancer based on clinical deta [33,34]. Some publications have even reported the prediction of distant metastasis using genetic assays [35].…”
Section: Discussionmentioning
confidence: 99%
“…The RecurIndex (RI) score of the 28-gene assay predicts the risk of local recurrence and distant metastasis based on the gene expression and clinicopathological factors (age, number of metastatic LNs, lympho-vascular invasion (LVI), ER status, tumor size, and grades) (18). Internal and external validations were also performed in different cohorts (19)(20)(21). The published results proved the prognostic value of the 28-gene assay, and hopefully, more validations will be carried out and eventually applied to clinical practice for Asian population.…”
Section: Are There Any Ethnic Differences In the Prognostic Assessmen...mentioning
confidence: 99%